A copper ion coordination cross-linked cellulose / polyvinyl alcohol composite film and a preparation method and application thereof
Patent Information
- Application Number
- CN202611163704.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-23
AI Technical Summary
上述方法虽然能够在一定程度上改善材料耐水性,但仍存在明显不足:表面涂层易在摩擦、剥离或长期水接触过程中失效,且难以增强材料体相网络;表面微结构改性对基底均匀性和加工条件要求较高,难以适用于大面积或复杂形状材料;疏水组分复合可能引起相容性差、相分离和界面缺陷;不可逆共价交联虽可增强网络稳定性,但不利于后续加工、再分散和闭环回收
[0030]本发明的有益效果是:本发明通过铜离子与纤维素/聚乙烯醇网络中的羟基氧位点发生Cu-O配位作用,在体相网络中引入金属-配体配位交联点,相比于传统的表面疏水涂层或简单抗菌剂掺混的方式,该配位交联点能够有效增强纤维素微纤维与聚乙烯醇链段之间的链间连接,提高复合膜的网络内聚力和应力传递能力,同时减少水可接触羟基位点,降低水分子对纤维素/聚乙烯醇氢键网络的破坏,从而抑制吸水溶胀和水诱导结构松弛,由此制备的复合膜在连续水浸泡条件下能够保持结构完整性,其可在水中稳定至少可达150天,干态拉伸强度可达约48MPa,完全水合状态下湿态拉伸强度可达约23MPa。此外,铜离子不仅能够作为配位交联节点增强材料网络,还能够赋予复合膜对大肠杆菌和金黄色葡萄球菌的抗菌活性,使其用于水果包装时能够降低失水并抑制霉变。另外,本发明所利用的金属-配体配位作用具有一定可逆性,可通过酸处理实现解配位,并通过再成膜和再配位获得再生复合膜,从而实现闭环回收和循环利用。本发明的制备过程主要基于水相处理、环境条件干燥和铜离子配位交联,不依赖熔融加工、高温热压或高压致密化,具有工艺温和、功能集成和规模化应用等特点。
Smart Images

Figure CN122958746A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film, its preparation method, and its application, belonging to the field of packaging materials technology. Background Technology
[0002] Petroleum-based plastic films are widely used in food packaging, logistics and transportation, disposable products, and everyday consumer goods packaging due to their good processability, flexibility, and water resistance. However, petroleum-based plastics are non-renewable and difficult to degrade naturally after disposal, easily accumulating in the environment over a long period and causing microplastic and nanoplastic pollution.
[0003] Cellulose is a naturally abundant renewable polymer, widely found in wood and other lignocellulosic biomass, characterized by its wide availability, biodegradability, ease of processing, and good film-forming properties. Among these, lignocellulosic microfibers offer advantages over nanocellulose, including simpler preparation processes, lower energy consumption, and greater potential for large-scale production, making them promising candidates for sustainable packaging materials. However, cellulose molecules contain numerous hydroxyl groups, and cellulose-based films typically rely on hydrogen bonding to form a network structure. While this hydrogen-bonded network helps maintain material strength in a dry state, it is easily weakened by water molecules in an aqueous environment, leading to water absorption and swelling, decreased inter-chain connectivity, and reduced wet mechanical properties. Furthermore, cellulose microfiber materials suffer from relatively large fiber sizes, low specific surface areas, and limited inter-fiber contact density and stress transfer efficiency, further restricting their application as a high-performance plastic alternative.
[0004] To improve the water resistance of cellulose-based materials, existing technologies typically employ methods such as hydrophobic surface coatings, surface microstructure construction, hydrophobic polymer or inorganic particle composites, and chemical modification. While these methods can improve water resistance to some extent, they still have significant shortcomings: surface coatings are prone to failure during friction, peeling, or prolonged water contact, and are unlikely to enhance the bulk network of the material; surface microstructure modification requires high substrate uniformity and processing conditions, making it unsuitable for large-area or complex-shaped materials; the composite of hydrophobic components may cause poor compatibility, phase separation, and interface defects; irreversible covalent crosslinking, while enhancing network stability, is detrimental to subsequent processing, redispersion, and closed-loop recycling. Furthermore, ordinary cellulose films, paper-based materials, and some biomass-based packaging materials often lack endogenous antibacterial functions, making them susceptible to microbial growth in humid or food packaging environments; simply adding external antibacterial agents may result in uneven dispersion, weak binding, uncontrollable release, or damage to mechanical properties. Summary of the Invention
[0005] To overcome the above-mentioned defects of the prior art, the present invention provides a copper ion coordination crosslinked cellulose / polyvinyl alcohol composite membrane, its preparation method and application. The prepared copper ion coordination crosslinked cellulose / polyvinyl alcohol composite membrane can effectively improve the water resistance, wet mechanical properties and antibacterial properties of the composite membrane by constructing metal-ligand coordination crosslinking points in the bulk phase network of the composite membrane.
[0006] The technical solution adopted in this invention is as follows: a method for preparing a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, wherein a cellulose / polyvinyl alcohol precursor membrane is immersed in an alkaline solution containing copper ions to perform copper ion coordination crosslinking, so that copper ions penetrate into the interior of the cellulose / polyvinyl alcohol precursor membrane and undergo Cu-O coordination with the hydroxyl oxygen sites in the cellulose and polyvinyl alcohol segments to form metal-ligand coordination crosslinking points. After the film turns a uniform blue color, it is taken out, washed until neutral, and then dried to obtain a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane.
[0007] Preferably, the cellulose / polyvinyl alcohol precursor membrane is immersed in the copper-containing alkaline solution for 1 to 6 days.
[0008] Preferably, the cellulose / polyvinyl alcohol precursor membrane is prepared by mixing an alkali-treated cellulose suspension with a polyvinyl alcohol solution, stirring until homogeneous, forming a film, and drying. The volume ratio of the alkali-treated cellulose suspension to the polyvinyl alcohol solution is 3:2.
[0009] Preferably, the film-forming method involves pouring the mixture of the treated cellulose suspension and the polyvinyl alcohol solution into a corresponding mold and drying it under environmental conditions to form a film.
[0010] Preferably, the alkali-treated cellulose suspension is prepared by sequentially treating the woody raw material with sodium chlorite solution for lignin removal and sodium hydroxide solution for alkali removal. After lignin removal and alkali treatment, the woody raw material forms wood-derived cellulose microfibers, and the solid content of the alkali-treated cellulose suspension is 1.5 wt%.
[0011] Specifically, the wood raw material is added to a sodium chlorite solution for delignification treatment to obtain delignified wood raw material. The delignified wood raw material is then added to a sodium hydroxide solution for alkali treatment to remove residual hemicellulose and promote fiber dissociation. After treatment, it is washed until neutral to obtain the alkali-treated cellulose suspension.
[0012] Preferably, the wood raw material is poplar wood shavings, poplar wood pellets, or poplar processing residues.
[0013] Preferably, the sodium chlorite solution has a mass fraction of 2wt% to 10wt%.
[0014] Preferably, when performing delignification treatment on the woody raw material, acetic acid is used to adjust the pH to 4.6.
[0015] Preferably, when performing delignification treatment on the wood raw material, the treatment temperature is 90°C and the treatment time is 5 hours.
[0016] Preferably, the sodium hydroxide solution used for alkaline treatment has a mass fraction of 10 wt%.
[0017] Preferably, the alkali treatment time is 12 hours, and the product is washed with deionized water after alkali treatment.
[0018] Preferably, the polyvinyl alcohol solution has a mass fraction of 5 wt% to 20 wt%.
[0019] Preferably, the polyvinyl alcohol solution is prepared by dissolving polyvinyl alcohol in deionized water under heating and stirring conditions.
[0020] Preferably, the polyvinyl alcohol is PVA-1799.
[0021] Preferably, the preparation conditions for the polyvinyl alcohol are continuous stirring at 90°C for 2 hours.
[0022] Preferably, the alkaline solution containing copper ions is prepared by immersing a copper source in a sodium hydroxide solution until a stable dark blue solution is formed.
[0023] Preferably, the sodium hydroxide solution used to prepare the alkaline solution containing copper ions has a mass fraction of 5wt% to 20wt%, and is prepared by adding sodium hydroxide to deionized water.
[0024] Preferably, the copper source is copper wire.
[0025] A copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane is prepared by any of the preparation methods of copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membranes disclosed in this invention. The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane comprises wood-derived cellulose microfibers, polyvinyl alcohol, and copper ions. The hydroxyl oxygen sites in the copper ion cellulose and polyvinyl alcohol segments undergo Cu-O coordination to form metal-ligand coordination crosslinking sites.
[0026] Preferably, the copper content of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film is 2wt%~4.8wt%.
[0027] The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film prepared by any of the methods disclosed in this invention, or the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film disclosed in this invention, can be used as packaging materials.
[0028] Preferably, the packaging materials include sustainable packaging materials, food preservation packaging materials, wet environment packaging materials, water contact environment film materials, and antimicrobial packaging materials.
[0029] The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared by any of the methods disclosed in this invention, or the method for recycling and regenerating the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane disclosed in this invention, includes the following steps: Step 1: Break the used or discarded copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane into small pieces; Step 2: Place the small pieces in an acidic solution to dissociate the Cu-O coordination and remove some copper ions, thereby obtaining a redispersible cellulose / polyvinyl alcohol matrix; Step 3: Redisperse the cellulose / polyvinyl alcohol matrix and form a film; Step 4: Immerse the re-formed film in the alkaline solution containing copper ions to perform copper ion coordination crosslinking, thereby obtaining a regenerated copper ion coordination crosslinked cellulose / polyvinyl alcohol composite film.
[0030] The beneficial effects of this invention are as follows: This invention introduces metal-ligand coordination crosslinking points into the bulk network by copper ions interacting with the hydroxyl oxygen sites in the cellulose / polyvinyl alcohol network via Cu-O coordination. Compared to traditional methods such as surface hydrophobic coatings or simple antibacterial agent mixing, these coordination crosslinking points effectively enhance the interchain connections between cellulose microfibers and polyvinyl alcohol segments, improving the network cohesion and stress transfer capacity of the composite film. Simultaneously, it reduces the number of water-accessible hydroxyl sites, minimizing the damage of water molecules to the cellulose / polyvinyl alcohol hydrogen bond network, thereby inhibiting water absorption swelling and water-induced structural relaxation. The resulting composite film maintains structural integrity under continuous water immersion conditions, remaining stable in water for at least 150 days. Its dry tensile strength reaches approximately 48 MPa, and its wet tensile strength in a fully hydrated state reaches approximately 23 MPa. Furthermore, copper ions not only act as coordination crosslinking nodes to reinforce the network but also impart antibacterial activity against *Escherichia coli* and *Staphylococcus aureus*, reducing water loss and inhibiting mold growth when used in fruit packaging. Furthermore, the metal-ligand coordination utilized in this invention is reversible to some extent. Decoupling can be achieved through acid treatment, and a regenerated composite membrane can be obtained through re-film formation and recoupling, thereby achieving closed-loop recycling and reuse. The preparation process of this invention is mainly based on aqueous phase treatment, environmental drying, and copper ion coordination crosslinking, without relying on melt processing, high-temperature hot pressing, or high-pressure densification. It features mild processing, functional integration, and large-scale application. Attached Figure Description
[0031] Figure 1 This is a flowchart of the method for preparing the copper ion coordinated crosslinked cellulose / polyvinyl alcohol composite membrane of the present invention; Figure 2 This is a flowchart of the method for recycling and regenerating the copper ion coordinated crosslinked cellulose / polyvinyl alcohol composite membrane of the present invention; Figure 3 These are scanning electron microscope images of delignified cellulose and alkali-treated cellulose prepared in Example 1 of the present invention; Figure 4 This is a cross-sectional scanning electron microscope image of the cellulose / polyvinyl alcohol precursor membrane and the cellulose / polyvinyl alcohol composite membrane crosslinked by copper ions prepared in Example 1 of the present invention. Figure 5 This is an energy spectrum distribution diagram of copper element in the cellulose / polyvinyl alcohol precursor membrane and the cellulose / polyvinyl alcohol composite membrane with copper ion coordination crosslinking prepared in Example 1 of the present invention; Figure 6 This is a comparison chart of the water immersion stability of the cellulose / polyvinyl alcohol precursor membrane prepared in Example 1 of the present invention and the cellulose / polyvinyl alcohol composite membrane with copper ion coordination crosslinking. Figure 7The graphs show the water absorption rate and thickness expansion of the cellulose / polyvinyl alcohol precursor membrane and the cellulose / polyvinyl alcohol composite membrane crosslinked by copper ions prepared in Example 1 of this invention. Figure 8 These are wet tensile test results of the cellulose / polyvinyl alcohol precursor membrane and the copper ion coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in Example 1 of the present invention. Figure 9 This is a test diagram of the antibacterial properties of the cellulose / polyvinyl alcohol precursor membrane and the copper ion coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in Example 1 of the present invention against Escherichia coli and Staphylococcus aureus. Figure 10 This is a cell compatibility test diagram of the cellulose / polyvinyl alcohol precursor membrane and the cellulose / polyvinyl alcohol composite membrane crosslinked by copper ions prepared in Example 1 of the present invention. Figure 11 This is a graph showing the copper ion content in the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membranes prepared in Examples 1, 2, 3 and 4 of the present invention; Figure 12 This is a diagram showing the mechanical properties of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane after regeneration, prepared in Example 1 of this invention. Figure 13 These are application examples and comparative examples of the preservation effect diagrams of the present invention. Detailed Implementation
[0032] See Figure 1 This invention discloses a method for preparing a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, comprising the following steps: S1. Preparation of wood-derived cellulose suspension: The wood raw material is subjected to a process of delignification treatment with sodium chlorite solution and alkali treatment with sodium hydroxide solution. Specifically, the wood raw material is added to sodium chlorite solution for delignification treatment to obtain delignified wood raw material. Then, the delignified wood raw material is added to sodium hydroxide solution for alkali treatment to remove residual hemicellulose and promote fiber dissociation. After treatment, it is washed until neutral to obtain an alkali-treated cellulose suspension. The solid content of the alkali-treated cellulose suspension is preferably 1.5 wt%.
[0033] The preferred wood raw material is poplar wood shavings, poplar wood pellets, or poplar processing residues. The wood raw material is then treated with delignification and alkali to form wood-derived cellulose microfibers.
[0034] The mass fraction of the sodium chlorite solution can be 2wt% to 10wt%, for example, 2wt%, 3wt%, 5wt%, 8wt% or 10wt%, preferably 5wt%.
[0035] When performing delignification treatment on the woody raw material, acetic acid is preferably used to adjust the pH to 4.6. The delignification treatment is preferably performed at a temperature of 90°C for 5 hours.
[0036] The sodium hydroxide solution used for alkali treatment preferably has a mass fraction of 10 wt%. The alkali treatment time is preferably 12 hours, and washing with deionized water is preferred after alkali treatment.
[0037] The purpose of treating wood raw materials with sodium chlorite solution for lignin removal and sodium hydroxide solution for alkaline treatment is to remove lignin and some hemicellulose components from the wood raw materials, expose the cellulose skeleton in the wood cell wall, and promote the decomposition and dissociation of cellulose components to form cellulose microfibers, thereby providing a dispersible wood-based cellulose raw material for subsequent mixing with polyvinyl alcohol to form a film.
[0038] Poplar wood raw materials are mainly composed of cellulose, hemicellulose, and lignin. Lignin, as an aromatic polymer component, fills and binds the cell wall structure, limiting the exposure of the cellulose skeleton and fiber dissociation. Sodium chlorite can oxidize and remove lignin under acidic conditions, exposing the cellulose components in the cell wall. Subsequent treatment with sodium hydroxide solution can further remove residual hemicellulose and weaken the interactions between cellulose microfibers and between cellulose and other matrix components, thereby promoting fiber dissociation and dispersion, forming an alkaline-treated cellulose suspension with a certain aspect ratio and entanglement characteristics.
[0039] S2. Preparation of polyvinyl alcohol solution: Polyvinyl alcohol is added to deionized water and dissolved under heating and stirring conditions to obtain a polyvinyl alcohol solution.
[0040] The mass fraction of the polyvinyl alcohol solution can be 5wt% to 20wt%, for example, 5wt%, 10wt%, 15wt% or 20wt%, preferably 10wt%.
[0041] The preferred preparation conditions are continuous stirring at 90°C for 2 hours.
[0042] The polyvinyl alcohol is preferably PVA-1799.
[0043] The purpose of preparing a uniform polyvinyl alcohol solution is to enable polyvinyl alcohol to be fully dispersed in the cellulose suspension in subsequent steps, and to participate in the construction of the cellulose / polyvinyl alcohol precursor membrane as a film-forming matrix and a hydroxyl-rich interacting component.
[0044] Polyvinyl alcohol (PVA) molecules contain a large number of hydroxyl groups, exhibiting excellent water solubility and film-forming properties. Under heating and stirring conditions, PVA segments gradually swell and dissolve in water, forming a homogeneous polymer solution. When this PVA solution is subsequently mixed with a cellulose suspension, the hydroxyl groups can form hydrogen bonds with the hydroxyl groups on the surface of cellulose microfibers, thereby improving the interfacial bonding between cellulose microfibers and the continuity of the composite film.
[0045] S3. Preparation of cellulose / polyvinyl alcohol precursor membrane: The alkali-treated cellulose suspension is mixed with the polyvinyl alcohol solution, stirred evenly, formed into a film, and dried to obtain a cellulose / polyvinyl alcohol precursor membrane.
[0046] The preferred volume ratio of the alkali-treated cellulose suspension to the polyvinyl alcohol solution is 3:2. The film-forming method involves pouring the mixture of the treated cellulose suspension and the polyvinyl alcohol solution into a suitable mold and drying it under ambient conditions to form a film.
[0047] The preparation of cellulose / polyvinyl alcohol precursor membranes utilizes the film-forming properties and hydroxyl-rich characteristics of polyvinyl alcohol to assemble wood-derived cellulose microfibers into a continuous composite membrane structure, allowing the cellulose microfibers to embed into the polyvinyl alcohol matrix and form a hydrogen-bonded precursor network with certain mechanical strength and structural integrity.
[0048] The cellulose microfibers in alkali-treated cellulose suspensions contain a large number of hydroxyl groups on their surface, and polyvinyl alcohol (PVA) molecular chains are also rich in hydroxyl groups. When the two are mixed, during water evaporation and drying to form a film, numerous hydrogen bonds can form between cellulose microfibers, between PVA segments, and between cellulose microfibers and PVA segments. These hydrogen bonds help improve the interfacial contact and network cohesion between cellulose microfibers, transforming the originally loose cellulose microfiber network into a more continuous and dense cellulose / PVA precursor membrane structure. Simultaneously, PVA, as a film-forming matrix, can fill the gaps between cellulose microfibers, improving the overall continuity and processability of the composite membrane.
[0049] S4. Prepare an alkaline solution containing copper ions: Sodium hydroxide solution is prepared by adding sodium hydroxide to deionized water; then copper source is immersed in the sodium hydroxide solution until a stable dark blue solution is formed, resulting in an alkaline solution containing copper ions (or Cu(II) loaded alkaline solution).
[0050] The mass fraction of sodium hydroxide solution used to prepare the alkaline solution containing copper ions can be 5wt% to 20wt%, for example, 5wt%, 10wt%, 15wt% or 20wt%, preferably 20wt%.
[0051] The copper source is preferably copper wire.
[0052] The purpose of preparing an alkaline solution containing copper ions is to enable copper species to exist in a strongly alkaline environment in a form that can participate in coordination, and to provide a reaction environment for the deprotonation of hydroxyl groups and Cu-O coordination in the cellulose / polyvinyl alcohol precursor membrane.
[0053] In concentrated sodium hydroxide solution, Cu(II)-containing copper species can gradually form on the surface of copper wires, giving the solution a deep blue color. This deep blue color can serve as a macroscopic characterization of Cu(II) species formation. The concentrated alkaline environment is beneficial on the one hand to the partial deprotonation of hydroxyl groups in the subsequent cellulose / polyvinyl alcohol network, generating oxygen sites that can coordinate with copper ions; on the other hand, it is beneficial to the penetration and diffusion of copper species in the membrane, thus providing conditions for constructing a bulk Cu-O coordination crosslinking network.
[0054] S5. Preparation of composite membranes by copper ion coordination crosslinking: The cellulose / polyvinyl alcohol precursor membrane is immersed in an alkaline solution containing copper ions for copper ion coordination crosslinking. This allows copper ions to penetrate the interior of the cellulose / polyvinyl alcohol precursor membrane and undergo Cu-O coordination with the hydroxyl oxygen sites in the cellulose and polyvinyl alcohol segments, forming metal-ligand coordination crosslinking points. This enhances the interchain connectivity of the cellulose / polyvinyl alcohol network and reduces the water-accessible hydroxyl sites. After the film turns a uniform blue color, it is removed, thoroughly washed with deionized water until neutral, and then dried at room temperature to obtain a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane.
[0055] The cellulose / polyvinyl alcohol precursor membrane can be soaked in the alkaline solution containing copper ions for 1 to 6 days, for example, 1, 2, 3, 4, 5 or 6 days, preferably 5 days.
[0056] In S5, through Cu 2+ The Cu-O coordination is formed with the hydroxyl oxygen sites in the cellulose / polyvinyl alcohol network, introducing metal-ligand coordination crosslinking points into the bulk phase network of the composite membrane, thereby improving the water resistance, wet structural integrity and antibacterial properties of the composite membrane.
[0057] Cellulose / polyvinyl alcohol precursor films primarily rely on hydrogen bonding to maintain their network structure. However, this hydrogen-bonded network is susceptible to swelling and weakening of interchain connections due to competition from water molecules in an aqueous environment. In a strongly alkaline solution supported on Cu(II), some hydroxyl groups on the cellulose and polyvinyl alcohol segments undergo deprotonation, forming bonds that can bind with Cu. 2+ Coordinated oxygen sites. With Cu 2+Diffusion into the membrane interior allows copper to form Cu-O coordination crosslinking points with the aforementioned oxygen sites, further enhancing the existing hydrogen-bonded cellulose / polyvinyl alcohol network. This Cu-O coordination reduces the number of hydroxyl sites accessible to water molecules, minimizing water molecule damage to the hydrogen bond network and inhibiting water absorption swelling and water-induced structural relaxation. Furthermore, it acts as an interchain bridging point, strengthening the connection between cellulose microfibers and polyvinyl alcohol segments, improving stress transfer capacity and structural stability under wet conditions. Simultaneously, copper species impart antibacterial activity to the composite membrane, enabling it to inhibit the growth of bacteria such as Escherichia coli and Staphylococcus aureus. The washing process to neutrality removes residual alkali and unstable copper species, while room temperature drying allows the copper-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane to form a stable macroscopic membrane material.
[0058] This invention also discloses a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, which is prepared by any of the preparation methods of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane disclosed in this invention. The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane includes wood-derived cellulose microfibers, polyvinyl alcohol and copper ions. The hydroxyl oxygen sites in the copper ion cellulose and polyvinyl alcohol segments undergo Cu-O coordination to form metal-ligand coordination crosslinking sites.
[0059] The copper content of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film can be 2wt% to 4.8wt%, for example, 2wt%, 3wt%, 3.5wt%, 4wt% or 4.8wt%, preferably 4.8wt%.
[0060] The present invention also discloses the application of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film as a packaging material.
[0061] The packaging materials preferably include sustainable packaging materials, food preservation packaging materials, wet environment packaging materials, water contact environment film materials, and antimicrobial packaging materials. The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film is particularly suitable for use as a fruit preservation packaging material.
[0062] In practical applications, the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film can be prepared into packaging films, packaging bags, cup-shaped packaging structures, straw-shaped structures, or tray-shaped packaging structures, etc., according to the usage requirements.
[0063] See Figure 2 The present invention also discloses a method for recycling and regenerating the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, comprising the following steps: Step 1: Break the used or discarded copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane into small pieces; Step 2: Place the small pieces in an acidic solution to dissociate the Cu-O coordination and remove some copper ions, thereby obtaining a redispersible cellulose / polyvinyl alcohol matrix; Step 3: Redisperse the cellulose / polyvinyl alcohol matrix in water and reform the film; Step 4: Immerse the re-formed film in the alkaline solution containing copper ions to perform copper ion coordination crosslinking, thereby obtaining a regenerated copper ion coordination crosslinked cellulose / polyvinyl alcohol composite film.
[0064] In practical applications of recycling and regenerating the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, steps two to four can be repeated multiple times, for example, two or three times.
[0065] The following are examples of the preparation of cellulose / polyvinyl alcohol composite membranes with copper ion coordination crosslinking: Example 1: S1: Poplar wood particles were placed in a 5 wt% NaClO2 solution, the pH was adjusted to 4.6 with acetic acid, and the solution was treated at 90 °C for 5 h to obtain delignified wood particles; the delignified wood particles were then placed in a 10 wt% NaOH solution and treated under continuous stirring for 12 h to remove residual hemicellulose and promote fiber dissociation. After treatment, the solution was washed with deionized water until neutral to obtain an alkali-treated cellulose suspension with a solid content of 1.5 wt%.
[0066] Scanning electron microscopy (SEM) images of delignified cellulose and alkali-treated cellulose are shown below. Figure 3 As shown, by Figure 3 It can be seen that alkali treatment further dissociates the residual hemicellulose matrix, releasing highly entangled cellulose microfibers, which reduce their diameter and increase their aspect ratio.
[0067] S2: Add PVA to deionized water at 90°C. o After stirring continuously at C for 2 hours, a PVA solution with a mass fraction of 10 wt% was obtained.
[0068] S3: The alkali-treated cellulose suspension obtained in S1 and the PVA solution obtained in S2 are mixed at a volume ratio of 3:2, stirred until uniform, then poured into a mold and dried under ambient conditions to obtain a cellulose / polyvinyl alcohol precursor membrane.
[0069] S4: Dissolve 200g of NaOH in deionized water to prepare a 20wt% NaOH solution; immerse 10g of copper wire in the NaOH solution until a stable deep blue color is formed, thus obtaining an alkaline solution containing copper ions (or a Cu(II) loaded NaOH solution).
[0070] S5: Immerse the cellulose / polyvinyl alcohol precursor membrane obtained in S3 into the alkaline solution containing copper ions obtained in S4 for 5 days until the membrane turns a uniform blue color; then remove the membrane, wash it with deionized water until neutral, and dry it at room temperature to obtain a copper ion coordinated crosslinked cellulose / polyvinyl alcohol composite membrane.
[0071] Scanning electron microscopy (SEM) was performed on the cellulose / polyvinyl alcohol precursor membrane prepared in S3 and the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in S5. The resulting SEM images are shown below. Figure 4 As shown, by Figure 4 It can be seen that the cellulose / polyvinyl alcohol precursor membrane exhibits a compact and continuous cross-sectional morphology, with cellulose microfibers embedded in a polyvinyl alcohol-rich matrix; after copper ion coordination crosslinking, the composite membrane still maintains a complete and dense microstructure without obvious structural collapse.
[0072] Energy dispersive spectroscopy (EDS) analysis was performed on the copper element in the prepared copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane. The obtained EDS distribution of copper element is shown in the figure below. Figure 5 As shown, by Figure 5 It can be seen that copper is uniformly distributed inside the composite membrane.
[0073] The cellulose / polyvinyl alcohol precursor membrane prepared in S3 and the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in S5 were respectively immersed in water for water immersion stability testing. The water immersion stability of the two was compared as follows: Figure 6 As shown, by Figure 6 It can be seen that the cellulose / polyvinyl alcohol precursor membrane exhibited significant dimensional deformation, curling, and internal structural expansion after immersion in water for 7 days; in contrast, the copper ion coordination crosslinked composite membrane basically maintained its structural integrity and showed less deformation, indicating that its water resistance stability was significantly improved.
[0074] The cellulose / polyvinyl alcohol precursor membrane prepared in S3 and the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in S5 were respectively immersed in water for water absorption and thickness expansion tests. The test results are as follows: Figure 7 As shown, by Figure 7 It was found that after soaking for 30 minutes, the moisture content of the cellulose / polyvinyl alcohol precursor membrane rapidly increased to 67.586%, approximately 1.7 times that of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane (38.993%). After immersion, the cellulose / polyvinyl alcohol precursor membrane exhibited numerous honeycomb-like pores due to water-induced swelling and network expansion, while the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane maintained a relatively dense structure without significant pores. This indicates that the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane effectively inhibits water absorption, swelling, and water-induced structural relaxation compared to the cellulose / polyvinyl alcohol precursor membrane.
[0075] Wet tensile properties were tested on the cellulose / polyvinyl alcohol precursor membrane prepared in S3 and the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in S5. The test results are as follows: Figure 8 As shown, by Figure 8 It can be seen that, under wet conditions, the tensile properties of the cellulose / polyvinyl alcohol composite membrane with copper ion coordination crosslinking are significantly better than those of the cellulose / polyvinyl alcohol precursor membrane. This indicates that copper ion coordination crosslinking helps to reduce the damage of hydration to the membrane network and improve the wet mechanical stability of the composite membrane.
[0076] The antibacterial properties of the cellulose / polyvinyl alcohol precursor membrane prepared in S3 and the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in S5 were tested against Escherichia coli and Staphylococcus aureus. The antibacterial performance of Escherichia coli (E. coli) was tested. E. coli ) and Staphylococcus aureus ( S. aureus Representative strains of Gram-negative and Gram-positive bacteria were used, respectively, to evaluate the antibacterial activity of the samples. The bacterial suspensions were diluted with fresh culture medium to an optical density (OD). 600 The concentration was approximately 0.1. Subsequently, 2 mL of the diluted bacterial suspension was transferred to each well of a 12-well plate containing the test sample, and incubated at 37°C with shaking at 200 rpm for 3 hours. After incubation, the bacterial suspension was collected and serially diluted tenfold using sterile phosphate-buffered saline (PBS). 30 μL of each dilution was plated onto LB agar plates, with three replicates for each dilution. After overnight incubation at 37°C, colonies were photographed, and quantitative analysis was performed using colony forming unit (CFU) counting. The test results are as follows: Figure 9 As shown, by Figure 9 It can be seen that, compared with the cellulose / polyvinyl alcohol precursor membrane, the colony density of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane after treatment is significantly reduced, indicating that it has significant antibacterial activity.
[0077] Cell compatibility was tested on the cellulose / polyvinyl alcohol precursor membrane prepared in S3 and the copper-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in S5. HEK293T cells and Cell Counting Kit-8 (CCK-8) were used to assess the cell compatibility. HEK293T cells were seeded in 96-well plates and cultured at 37°C for 24 h in a humidified incubator containing 5% CO2 to allow cell adhesion. Subsequently, aqueous extracts of both membranes were added to the corresponding wells and co-incubated with the cells for 24 h. Each experimental group had three parallel wells. After treatment, 10 μL of CCK-8 reagent was added to each well, and incubation continued at 37°C for 4 h. The absorbance at 450 nm was measured using a microplate reader. Cell viability was calculated based on the measured absorbance values and expressed as a percentage of the untreated control group. The test results are as follows: Figure 10 As shown, by Figure 10 It can be seen that the cells cultured in the extract of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane mainly exhibited uniform and strong green fluorescence, with only a small amount of weak red fluorescence signal; there was no significant difference between the cellulose / polyvinyl alcohol precursor membrane, the copper ion-coordinated crosslinked composite membrane and the blank control group, indicating that the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane has good cell compatibility under the test conditions.
[0078] Example 2: The difference between this embodiment and Embodiment 1 is that: In S5, the cellulose / polyvinyl alcohol precursor membrane obtained in S3 is immersed in the alkaline solution containing copper ions obtained in S4 for 1 day.
[0079] Apart from the differences mentioned above, the other implementation steps and methods are the same as in Example 1.
[0080] Example 3: The difference between this embodiment and Embodiment 1 is that: In S5, the cellulose / polyvinyl alcohol precursor membrane obtained in S3 is immersed in the alkaline solution containing copper ions obtained in S4 for 3 days.
[0081] Apart from the differences mentioned above, the other implementation steps and methods are the same as in Example 1.
[0082] Example 4: The difference between this embodiment and Embodiment 1 is that: In S5, the cellulose / polyvinyl alcohol precursor membrane obtained in S3 is immersed in the alkaline solution containing copper ions obtained in S4 for 6 days.
[0083] Apart from the differences mentioned above, the other implementation steps and methods are the same as in Example 1.
[0084] The copper ion content of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membranes prepared in Examples 1, 2, 3, and 4 was tested, and the test results are as follows: Figure 11 As shown, by Figure 11 It can be seen that as the soaking time is extended, the copper ion content in the composite membrane gradually increases, and reaches a saturation value of about 4.8 wt% after 5 days of soaking, indicating that the optimal value of copper content in the composite membrane is 4.8 wt%.
[0085] The following are examples of recycling and regeneration of copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membranes: Example 5: Step 1: Break the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in Example 1 after use or disposal into 0.5 cm pieces. 2 -1.0cm2 Small pieces; Step 2: Place the small pieces in a 1 mol / L hydrochloric acid solution for 2 minutes to dissociate the Cu-O coordination and remove some copper ions, thereby obtaining a redispersible cellulose / polyvinyl alcohol matrix. Step 3: Redisperse the cellulose / polyvinyl alcohol matrix in water and reform the film; Step 4: Immerse the re-formed film in the alkaline solution containing copper ions (the same alkaline solution containing copper ions as in Example 1) to perform copper ion coordination crosslinking, and obtain a regenerated copper ion coordination crosslinked cellulose / polyvinyl alcohol composite film.
[0086] Example 6: The difference between this embodiment and embodiment 5 is as follows: Repeat steps two through four twice.
[0087] Apart from the differences mentioned above, the implementation steps and methods are the same as in Example 5.
[0088] Example 7: The difference between this embodiment and embodiment 5 is as follows: Repeat steps two through four three times.
[0089] Apart from the differences mentioned above, the implementation steps and methods are the same as in Example 5.
[0090] The mechanical properties of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared in Example 1, as well as the composite membranes recycled in Examples 5, 6, and 7, were tested. The test results are as follows: Figure 12 As shown, by Figure 12 It can be seen that after multiple regeneration cycles, the regenerated composite membrane can still maintain its mechanical properties well. After three complete regeneration cycles, the dry tensile strength of the recycled composite membrane can still be maintained at 42 MPa, and the wet tensile strength is 17.9 MPa, indicating that the regenerated composite membrane has a certain degree of reversibility and can be recycled and reused.
[0091] Application example: The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film prepared in Example 1 was used for strawberry packaging and preservation.
[0092] Comparative example: Commercial polyethylene film was used to package and preserve the same strawberries as in the application example.
[0093] Application examples and comparative examples of the preservation effect on strawberries, such as... Figure 13 As shown, by Figure 13It can be seen that strawberries packaged in commercial polyethylene film showed obvious fungal infection after 5 days of storage, while strawberries packaged in copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film did not show obvious mold growth during storage, indicating that its preservation ability is significantly higher than that of commercial polyethylene film.
[0094] Unless otherwise specified or further limited to one preferred or optional technical means being another, the preferred and optional technical means disclosed in this invention can be arbitrarily combined to form several different technical solutions.
Claims
1. A method for preparing a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, characterized in that... The cellulose / polyvinyl alcohol precursor membrane was immersed in an alkaline solution containing copper ions to perform copper ion coordination crosslinking. This allowed the copper ions to penetrate into the interior of the cellulose / polyvinyl alcohol precursor membrane and undergo Cu-O coordination with the hydroxyl oxygen sites in the cellulose and polyvinyl alcohol segments, forming metal-ligand coordination crosslinking points. After the membrane turned a uniform blue color, it was removed, washed until neutral, and then dried to obtain a copper ion coordinated crosslinked cellulose / polyvinyl alcohol composite membrane.
2. The method for preparing the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane according to claim 1, characterized in that... The cellulose / polyvinyl alcohol precursor membrane is prepared by mixing an alkali-treated cellulose suspension with a polyvinyl alcohol solution, stirring until homogeneous, forming a film, and then drying. The volume ratio of the alkali-treated cellulose suspension to the polyvinyl alcohol solution is 3:
2.
3. The method for preparing the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane according to claim 2, characterized in that... The alkali-treated cellulose suspension is prepared by sequentially treating woody raw materials with sodium chlorite solution for lignin removal and sodium hydroxide solution for alkali treatment. The solid content of the alkali-treated cellulose suspension is 1.5 wt%.
4. The method for preparing a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane according to claim 2, characterized in that... The polyvinyl alcohol solution has a mass fraction of 5wt% to 20wt%.
5. The method for preparing a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane according to claim 1, characterized in that... The alkaline solution containing copper ions is prepared by immersing a copper source in a sodium hydroxide solution until a stable dark blue solution is formed.
6. The method for preparing a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane according to claim 5, characterized in that... The sodium hydroxide solution used to prepare the copper ion-containing alkaline solution has a mass fraction of 5wt% to 20wt%.
7. A copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane, characterized in that... The cellulose / polyvinyl alcohol composite membrane prepared by the method described in any one of claims 1-6 is obtained.
8. The copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane according to claim 7, characterized in that... Its copper content is 2wt%~4.8wt%.
9. The application of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film prepared by the preparation method of the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film according to any one of claims 1-6, or the copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite film according to any one of claims 7-8, as a packaging material.
10. A method for recycling and regenerating a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane prepared by the method of any one of claims 1-6, or a copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane as described in any one of claims 7-8, characterized in that... Includes the following steps: Step 1: Break the used or discarded copper ion-coordinated crosslinked cellulose / polyvinyl alcohol composite membrane into small pieces; Step 2: Place the small pieces in an acidic solution to dissociate the Cu-O coordination and remove some copper ions, thereby obtaining a redispersible cellulose / polyvinyl alcohol matrix; Step 3: Redisperse the cellulose / polyvinyl alcohol matrix and form a film; Step 4: Immerse the re-formed film in the alkaline solution containing copper ions to perform copper ion coordination crosslinking, thereby obtaining a regenerated copper ion coordination crosslinked cellulose / polyvinyl alcohol composite film.